CAPACITY BUILDING AND THE PERFORMANCE OF WOMEN ENTREPRENEURS IN THE FEDERAL CAPITAL TERRITORY, ABUJA, NIGERIA - IBRAHIM , KADIRI KAYODE; IBRAHIM, ALASAN ALI; WACHUKWU, OFORBUIKE FRANCIS; CHIDIEBERE, NANCY UGOCHI; OJONUGWA, OKOLIKO EMMANUEL (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
The study is focused on investigating the Impact of Capacity Building on the Performance of Women Entrepreneurs in the Federal Capital Territory, Abuja, Nigeria. Specifically, it examines the effects of financial inclusion strategies, etworking skills, on the performance of women entrepreneurs in the FCT. Methodologically, the study adopts a causal survey research design, targeting all women entrepreneurs actively conducting businesses within the six area councils (Abaji, Abuja Municipal Area Council [AMAC], Bwari, Gwagwalada, Kuje, and Kwali) of the Federal Capital Territory, igeria. The Cochran sample size formula was initially utilized, resulting in a sample size of 384. Primary data was collected through a cross-sectional survey using a structured questionnaire. Out of 428 questionnaires distributed, 395 were completed and deemed suitable for analysis. Data analysis involved the use of simple percentages, frequency distribution tables, and Partial Least Squares Structural Equation Modelling (PLS-SEM). The study found a positive and statistically significant effect of financial inclusion strategies, etworking skills, managerial abilities, entrepreneurial knowledge, on the performance of women entrepreneurs in the FCT. Among the recommendations, it is suggested that stakeholders, including government and educational institutions, provide entrepreneurial knowledge, particularly in marketing, management, and risk-taking